Content Analysis to Detect the Role Behaviors of Student in Online Discussion - Erlin .; Rahmiati .; Unang Rio (IAES Indonesia Section, 2014)
Online discussion is a powerful way to conduct online conversation and a significant component of online learning. Online discussion can provide a platform for online learners to communicate with one another easily, without the constraint of place and time. In an online discussion, the students communicate a common interest, exchange information, share ideas, and assist each other in text/transcript form. So far, content analysis is a popular method for analyzing transcripts. However, using content analysis in computer supported collaborative learning (CSCL) or computer mediated communication (CMC) research focused on the surface of the transcripts. Usually, content analysis is employed to categorize news article, product reviews and web pages. Therefore, this study proposed content analysis to a deeper level is to detect the role behavior of students in an online discussion based on a conversation in text form. The findings showed that this method provides more meaningful students’ interaction analysis in term of information on communication transcripts in online discussion. Educators can assess the contribution of students and can detect the role behavior of the student based on their conversation in transcript form; whether the role behavior as a mediator, motivator, informer, facilitator, or as a questioner.